MODIFIKASI ZAT PENGATUR TUMBUH DALAM BUDIDAYA JARINGAN UNTUK PERBANYAKAN BIBIT TEBU (Saccharum officinarum) - ., Supalal (BIOMA, 2015)
The aim was to obtained growth regulator effect in sugarcane multiplicationâs method. This research was expected to support particular sugarcane seedlings progam. The sugarcaneâs clone used VMC as explan for this research. The explan used medium MS0, MS + 0,5 mg/l BAP, MS + 1 mg/l BAP + 0,5 mg/l IBA, MS + 1,5 mg/l BAP + 0,5 mg/l IBA. Itâs repetead 3 times and consisted 3 samples. Researchâs parameters observed percentage and growing shootâs speed, budâs number, and shoots. MS + 1,5 mg/l BAP + 0,5 mg/l IBA had the best growthed and shootâs number among the other concetration; which was showed 66,67%.Keywords: tissue culture, growth regulator, sugarcane shoot